2011
DOI: 10.1093/humrep/der141
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in women with polycystic ovary syndrome initially randomized to receive laparoscopic electrocautery of the ovaries or ovulation induction with gonadotrophins

Abstract: In women with clomiphene-resistant PCOS, laparoscopic electrocautery of the ovaries is as effective as ovulation induction with FSH treatment in terms of live births, but reduces the need for ovulation induction or ART in a significantly higher proportion of women and increases the chance for a second child. Clinicians may use these data when informing clomiphene-resistant anovulatory women about treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 14 publications
1
19
0
4
Order By: Relevance
“…17,28 In a questionnaire based study of 168 women 8 to 12 years after being randomized to receive LOD or ovulation induction with gonadotrophins, 54% of the LOD-treated women had regular menstrual cycles and had an increased chance of having a second child. 29 Long-term follow-up of our cohort confirm that improvement in ovulation is sustained over time as demonstrated by the 52% of women that still had regular menstrual cycles after three to nine years. Although 45% of pregnancies occurred within the first year, 26% were achieved more than three years after surgery, suggesting a long lasting effect in fertility.…”
Section: Discussionsupporting
confidence: 77%
“…17,28 In a questionnaire based study of 168 women 8 to 12 years after being randomized to receive LOD or ovulation induction with gonadotrophins, 54% of the LOD-treated women had regular menstrual cycles and had an increased chance of having a second child. 29 Long-term follow-up of our cohort confirm that improvement in ovulation is sustained over time as demonstrated by the 52% of women that still had regular menstrual cycles after three to nine years. Although 45% of pregnancies occurred within the first year, 26% were achieved more than three years after surgery, suggesting a long lasting effect in fertility.…”
Section: Discussionsupporting
confidence: 77%
“…According to current evidence, including data on long term follow-up, laparoscopic ovarian drilling is recommended as an effective and economic second line treatment for ovulation induction in women with clomiphene resistant PCOS. [117][118][119][120][121][122] In conclusion, in women with WHO group II anovulation, both letrozole and the combination of clomiphene and metformin are superior to clomiphene alone in terms of ovulation and pregnancy. Letrozole is the only treatment showing a significantly higher rate of live birth when compared with clomiphene alone.…”
Section: Clinical Implications and Conclusionmentioning
confidence: 87%
“…Multiple gestation is a possible complication of induction of ovulation as a treatment of the anovulatory cycles in PCOS patients. Nahuis et al reported an incidence of twin pregnancy in PCOS patients in a randomised trial as 5 percent after being treated by laparoscopic electrocautery, and 8 percent after receiving recombinant-FSH [16]. In addition, Zhao et al studied the pregnancy outcome after in vitro maturation of immature oocytes, and found a significant increase in multiple gestation up to 30 percent, low birth weight, and preterm deliveries [17].…”
Section: Discussionmentioning
confidence: 99%